Accessing the WAN : CCNA exploration companion guide - Vachon, Bob.; Graziani, Rick (Indianapolis, Indiana : Cisco Press, 2008)
Accessing the WAN, CCNA Exploration Companion Guide is the official supplemental textbook for the Accessing the WAN course in the Cisco Networking Academy CCNA Exploration curriculum version 4. This course discusses the WAN technologies and network services required by converged applications in enterprise networks. The Companion Guide, written and edited by Networking Academy instructors, is designed as a portable desk reference to use anytime, anywhere. The book$1 (Bs features reinforce the material in the course to help you focus on important concepts and organize your study time for exams.s
Chapter 1 Introduction to WANs 1 Objectives 1Key Terms 1Introducing Wide-Area Networks (WANs) 3 What Is a WAN? 3 Why Are WANs Necessary? 5The Evolving Enterprise 5 Businesses and Their Networks 5 Small Office (Single LAN) 6 Campus (Multiple LANs) 6 Branch (WAN) 8 Distributed (Global) 9The Evolving Network Model 11 The Hierarchical Design Model 11 The Enterprise Architecture 13WAN Technology Concepts 17 WAN Technology Overview 17 WAN Physical Layer Concepts 18 WAN Data Link Layer Concepts 23 WAN Switching Concepts 26WAN Connection Options 29 WAN Link Connection Options 29 Dedicated Connection Link Options 31 Circuit-Switched Connection Options 32 Packet-Switched Connection Options 35I nternet Connection Options 38 Choosing a WAN Link Connection 44Summary 48Labs 49Check Your Understanding 50Challenge Questions and Activities 54 Chapter 2 PPP 55Objectives 55Key Terms 55Introducing Serial Communications 56 How Does Serial Communication Work? 56 Serial Communication Standards 59 TDM 61 Demarcation Point 66 Data Terminal Equipment and Data Communications Equipment 67 HDLC Encapsulation 72 Configuring HDLC Encapsulation 75 Troubleshooting Serial Interfaces 76PPP Concepts 83 Introducing PPP 83 PPP Layered Architecture 84 PPP Frame Structure 87 Establishing a PPP Session 88 Establishing a Link with LCP 89 NCP Explained 95 PPP Configuration Options 97 PPP Configuration Commands 98 Verifying a Serial PPP Encapsulation Configuration 101 Troubleshooting PPP Encapsulation 102 PPP Authentication Protocols 108 Password Authentication Protocol 109 Challenge Handshake Authentication Protocol (CHAP) 110 PPP Encapsulation and Authentication Process 112 Configuring PPP with Authentication 115 Troubleshooting a PPP Configuration with Authentication 118Summary 120Labs 120Check Your Understanding 122Challenge Questions and Activities 126 Chapter 3 Frame Relay 127Objectives 127Key Terms 127Introduction 128Basic Frame Relay Concepts 128 Introducing Frame Relay 128 Virtual Circuits 134 Frame Relay Encapsulation 140 Frame Relay Topologies 141 Frame Relay Address Mapping 145Configuring Frame Relay 152 Enabling Frame Relay Encapsulation 153 Configuring Static Frame Relay Maps 156Advanced Frame Relay Concepts 159 Solving Reachability Issues 159 Frame Relay Subinterfaces 161 Paying for Frame Relay 162 Frame Relay Flow Control 166Configuring Advanced Frame Relay 168 Configuring Frame Relay Subinterfaces 168 Verifying Frame Relay Operation 171 Troubleshooting Frame Relay Configuration 178Summary 180Labs 181Check Your Understanding 182Challenge Questions and Activities 188To Learn More 188 Chapter 4 Network Security 189Objectives 189Key Terms 189Introduction to Network Security 190 Why Is Network Security Important? 190 Common Security Threats 199 Types of Network Attacks 206 General Mitigation Techniques 219 The Network Security Wheel 226 The Enterprise Security Policy 229Securing Cisco Routers 232 Router Security Issues 232 Applying Cisco IOS Security Features to Routers 235Securing Router Network Services 250 Vulnerable Router Services and Interfaces 250 Securing Routing Protocols 256 Locking Down Your Router with Cisco AutoSecure 263Using Cisco SDM 264 Cisco SDM Overview 264 Configuring Your Router to Support SDM 265 Starting SDM 267 The SDM Interface 269 Cisco SDM Wizards 272 Locking Down a Router with SDM 272Secure Router Management 275 Maintaining Cisco IOS Software Images 275 Managing Cisco IOS Images 276 Managing Cisco IOS Images 283 Backing Up and Upgrading a Software Image 284 Recovering Software Images 288 Troubleshooting Cisco IOS Configurations 294 Recovering a Lost Password 297Summary 301Labs 301Check Your Understanding 302Challenge Questions and Activities 308 Chapter 5 ACLs 309Objectives 309Key Terms 309Using ACLs to Secure Networks 310 A TCP Conversation 310 Packet Filtering 313 What Is an ACL? 316 ACL Operation 318 Types of Cisco ACLs 322 How a Standard ACL Works 323 Numbering and Naming ACLs 323 Where to Place ACLs 324 General Guidelines for Creating ACLs 327Configuring Standard ACLs 327 Entering Criteria Statements 327 Configuring a Standard ACL 328 ACL Wildcard Masking 332 Applying Standard ACLs to Interfaces 339 Editing Numbered ACLs 343 Creating Standard Named ACLs 345 Monitoring and Verifying ACLs 346 Editing Named ACLs 347Configuring an Extended ACL 348 Extended ACLs 349 Configuring Extended ACLs 351 Applying Extended ACLs to the Interfaces 353 Creating Named Extended ACLs 355Configure Complex ACLs 357 What Are Complex ACLs? 357 Dynamic ACLs 358 Reflexive ACLs 360 Time-Based ACLs 363 Troubleshooting Common ACL Errors 364Summary 368Labs 368Check Your Understanding 369Challenge Questions and Activities 375 Chapter 6 Teleworker Services 377Objectives 377Key Terms 377Business Requirements for Teleworker Services 379 The Business Requirements for Teleworker Services 379 The Teleworker Solution 380Broadband Services 384 Connecting Teleworkers to the WAN 384 Cable 385 DSL 391 Broadband Wireless 396VPN Technology 401 VPNs and Their Benefits 402 Types of VPNs 405 VPN Components 407 Characteristics of Secure VPNs 408 VPN Tunneling 409 VPN Data Confidentiality and Integrity 410 IPsec Security Protocols 416Summary 419Labs 419Check Your Understanding 419Challenge Questions and Activities 423 Chapter 7 IP Addressing Services 429Objectives 429Key Terms 429Introduction 431DHCP 431 Introduction to DHCP 432 DHCP Operation 432 BOOTP and DHCP 435 Configuring a Cisco Router as a DHCP Server 440 Configuring a DHCP Client 447 DHCP Relay 449 Configuring a DHCP Server Using SDM 453 Troubleshooting DHCP Configuration 456Scaling Networks with NAT 460 What Is NAT? 462 Benefits and Drawbacks of Using NAT 468 Configuring Static NAT 470 Configuring Dynamic NAT 471 Configuring NAT Overload for a Single Public IP Address 473 Configuring NAT Overload for a Pool of Public IP Addresses 475 Configuring Port Forwarding 477 Verifying NAT and NAT Overload 479 Troubleshooting NAT and NAT Overload Configuration 483IPv6 485 Reasons for Using IPv6 489 IPv6 Addressing 493 IPv6 Transition Strategies 499 Cisco IOS Dual Stack 500 IPv6 Tunneling 502 Routing Configurations with IPv6 503 Configuring IPv6 Addresses 506 Configuring RIPng with IPv6 508Summary 512Labs 512Check Your Understanding 514Challenge Questions and Activities 522 Chapter 8 Network Troubleshooting 525Objectives 525Key Terms 525Establishing the Network Performance Baseline 526 Documenting Your Network 526 Network Documentation Process 533 Why Is Establishing a Network Baseline Important? 535 Steps for Establishing a Network Baseline 535Troubleshooting Methodologies and Tools 541 A General Approach to Troubleshooting 541 Using Layered Models for Troubleshooting 541 General Troubleshooting Procedures 544 Troubleshooting Methods 545 Gathering Symptoms 548 Troubleshooting Tools 551Review of WAN Communications 560 WAN Communications 560 Steps in WAN Design 561 WAN Traffic Considerations 562 WAN Topology Considerations 564 WAN Connection Technologies 567 WAN Bandwidth Considerations 568 Common WAN Implementations Issues 569 WAN Troubleshooting from an ISP's Perspective 570Network Troubleshooting 571 Physical Layer Troubleshooting 573 Data Link Layer Troubleshooting 577 Network Layer Troubleshooting 584 Transport Layer Troubleshooting 586 Application Layer Troubleshooting 589Summary 595Labs 595Check Your Understanding 596Challenge Questions and Activities 600Appendix 601Glossary 637
Includes bibliographical references and index.
Keywords: ELECTRONIC DATA PROCESSING PERSONNEL -- CERTIFICATION